The influence of the verb category on phrases in the valency position - Nováková, Andrea (Univerzita Pardubice, 2009)
This bachelor thesis deals with one of the specific features of the English verb, i.e. its possibility of occurrence with multiple complementation patterns (or, in other words, its multiple valency). First, the role of the verb in the sentence structure is closely examined, attention being pain especially to the way in which it selects its complements. In connection with this, the main verbal categories and syntactic functions of complements are discussed. Consequently, the work systematically studies the types of multiple complementation (valency) patterns in English, with the aim to find out which groups of verbs are likely to appear in which patterns. The focus is laid mainly on the semantics of such alternative constructions, on the relationship that holds between the verb and the complements and on the semantic roles which are associated with particular complements in particular functions. Finally, a text analysis is provided, which explores the frequency of the use of verbs with multiple valency patterns in the text and the factors which influence the choice of one or the other pattern with the verb.
Vliv slovesné kategorie na fráze ve valenční pozici
Keywords: slovesné kategorie; valenční pozice; multivalenční slovesa; verb categories; phrases; valency positions; multiple valency; fráze